Bilateral anterior and intermediate uveitis associated with parvovirus B19 infection in a pediatric patient: A case report - Sol Benbunan-Ferreiro; Jacques Bijon; Youssef Abdelmassih; Ana Clément (The Eastern Eye, 2026)
To describe a rare case of bilateral anterior and intermediate uveitis associated with parvovirus B19 infection in a pediatric patient and highlight diagnostic and therapeutic considerations. A 5-year-old boy presented with bilateral ocular pain, conjunctival hyperemia, and decreased visual acuity one week after hospitalization for systemic parvovirus B19 infection. Laboratory investigations excluded other infectious and autoimmune causes. Ophthalmologic examination revealed bilateral anterior chamber inflammation and vitritis. B-scan ultrasonography confirmed vitreous opacities. Polymerase chain reaction (PCR) analysis of anterior chamber fluid was performed to determine the etiologic agent. PCR testing detected parvovirus B19 DNA in the anterior chamber fluid, confirming the diagnosis. Initial treatment with intensive topical corticosteroids and cycloplegic agents failed to control inflammation. Subconjunctival dexamethasone injection resulted in rapid resolution of ocular inflammation and complete recovery of visual acuity. Parvovirus B19 should be considered in pediatric patients presenting with bilateral uveitis following systemic viral symptoms.